IoT Implementation for Hydroponic Water Monitoring Using Web-Based pH and TDS Sensors with Node-Red - Faisal, Mochammad; Bachtiar, Adnan Nuur; Darwis, Muhammad (Universitas Trilogi, 2025)
Due to land scarcity, rapid urbanization, and shrinking agricultural space, urban environments such as Jakarta face increasing agricultural challenges. By enabling efficient, soil-free cultivation in limited areas, hydroponics has emerged as a promising solution to address these issues. However, ensuring the consistency of the quality of hydroponic water systems, especially in terms of pH and total dissolved solids (TDS), is often done manually, which is ineffective and prone to human error. Several IoT-based solutions have been proposed; however, many rely on cloud services or mobile platforms, which limit accessibility in offline environments. This study introduces a scalable, internet-independent hydroponic water quality monitoring system that uses pH and TDS sensors connected to an ESP32 microcontroller. A Node-RED dashboard, accessible by a browser on a local network, is used by the system to display data in real time, using the MQTT protocol. The system, developed using the IoT Platform Design Methodology, underwent black-box testing to ensure that its data acquisition, transmission, and visualization were accurate. The results showed reliable performance without any functional errors. Classified as a Level 2 IoT system, it allows real-time monitoring without automation and the possibility of future expansion such as data storage and actuator control. The proposed system provides a practical and scalable solution for urban hydroponic farmers working in areas with limited internet connectivity.